Epidemiologic principles applied to injury prevention. - Coleman, Patrick J (Scandinavian Journal of Work, Environment & Health, 1981)
An analysis of injuries resulting from falls from ladders was carried out with the following objectives: to reveal potential causal factors of such injuries and to test epidemiologic concepts for improved design of a case-comparison study of such injuries. The study observations consisted of 1,419 workers injured in ladder-related accidents who responded to a Work Injury Report Survey questionnaire. This survey, designed jointly by the National Institute for Occupational Safety and Health, the Occupational Safety and Health Administration, and the Bureau of Labor Statistics, included questions on the design, composition, and condition of the ladder, the task being attempted by the injured, the condition of the worker`s shoes, the amount and kind of training, and other factors. After the identification of one group of injured workers (those injured while working from the ladder) as referents and a second group (those injured while climbing the ladder) as cases, a case-comparison analysis of other factors was carried out. The conclusions drawn were that the differences between the case and comparison groups were design- and task-related, while other factors were not directly comparable. This analysis points the way for designing a more carefully controlled study of such injuries.
Keywords: case referent study; epidemiologic principle; epidemiology; fall; injury prevention; ladder; Work Injury Report Survey